Description of Education Level and Health Behavior in Coastal Communities of the Sangihe Islands During the Covid-19 Pandemic - Kasaluhe, Meityn Disye; Sambeka, Yana (Institute Of Computer Science (IOCS), 2025)
Limited access to social services such as health services and education is a problem faced by communities in coastal areas. The COVID-19 outbreak that hit the world worsened conditions in coastal areas where coastal communities are increasingly vulnerable because the cost of adaptation to coastal damage is already huge, COVID-19 is very likely to increase these adaptation costs. This study aimed to obtain a description of the level of education and PHBS of coastal communities in the Sangihe Islands Regency during the COVID-19 pandemic. The type of research used was analytical survey research with a cross-sectional approach. The sampling method used was proportional sampling with a sample size of 125 respondents. In this study, most respondents were in the age category of 25-54 years (76.8%), the last education category included secondary education (49.6%), had PHBS knowledge in the good category (51.2%); positive attitudes (49.6%) and PHBS actions in the good category (49.6%.). The coastal communities in the Sangihe Islands Regency with the latest education level in the secondary education category had high knowledge about PHBS and had a positive attitude towards PHBS. In addition, they had good actions related to PHBS.